2014
DOI: 10.1002/art.38389
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Prevalence of Antineutrophil Cytoplasmic Antibodies in Infective Endocarditis

Abstract: Objective. Infective endocarditis (IE) mimics primary systemic vasculitis, and there are sporadic reports of positivity for antineutrophil cytoplasmic antibodies (ANCAs) among patients with IE. Because the frequency of ANCAs in IE is unknown, this study was undertaken to assess the seroprevalence of ANCAs in a large number of patients with IE.Methods. The study was conducted in the framework of a single-center prospective cohort study of incident IE cases. Demographic, clinical, laboratory, and microbiologic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 17 publications
0
77
1
8
Order By: Relevance
“…Langlois et al 100 reported ANCAs by IIF in 12 out of 50 patients (24%) with infective endocarditis; four patients had PR3-ANCAs, one patient had MPO-ANCAs and two patients had both PR3-ANCAs and MPO-ANCAs. Mahr et al 101 reported ANCA by IIF in 20 out of 109 patients (18%) with infective endocarditis (14 patients were positive for C-ANCA and six were positive for P-ANCA); of these, three patients had C-ANCA and PR3-ANCAs, two patients had C-ANCA and MPOANCAs, one patient had P-ANCA and MPO-ANCAs, one patient had just PR3-ANCAs and one patient had just MPO-ANCAs. Misdiagnosis of sub-acute bacterial endocarditis as AAV and initiation of inappropriate immunosuppressive therapy can have devastating consequences 102 .…”
Section: Recommandationmentioning
confidence: 99%
“…Langlois et al 100 reported ANCAs by IIF in 12 out of 50 patients (24%) with infective endocarditis; four patients had PR3-ANCAs, one patient had MPO-ANCAs and two patients had both PR3-ANCAs and MPO-ANCAs. Mahr et al 101 reported ANCA by IIF in 20 out of 109 patients (18%) with infective endocarditis (14 patients were positive for C-ANCA and six were positive for P-ANCA); of these, three patients had C-ANCA and PR3-ANCAs, two patients had C-ANCA and MPOANCAs, one patient had P-ANCA and MPO-ANCAs, one patient had just PR3-ANCAs and one patient had just MPO-ANCAs. Misdiagnosis of sub-acute bacterial endocarditis as AAV and initiation of inappropriate immunosuppressive therapy can have devastating consequences 102 .…”
Section: Recommandationmentioning
confidence: 99%
“…Etiologia często jest wieloczynnikowa [296,297]: (i) kompleksy immunologiczne i naczyniowe kłębuszkowe zapalenie nerek; (ii) zawał nerki, głównie na skutek zatorów septycznych, występujący w dowolnym czasie w przebiegu IZW; (iii) pogorszenie funkcji hemodynamicznych w przypadku HF lub ciężkiej posocznicy albo w okresie pooperacyjnym; (iv) nefrotoksyczność antybiotyków (ostre śródmiąższowe zapalenie nerek), wyraźnie związane ze stosowaniem aminoglikozydów, wankomycyny (toksyczne działanie synergistyczne z aminoglikozydami), a nawet benzylopenicyliny w wysokich dawkach; (v) nefrotoksyczność środków kontrastowych stosowanych w diagnostyce obrazowej.…”
Section: Ostra Niewydolność Nerekunclassified
“…c-ANCA are most often encountered in SBE, but p-ANCA are also described. Recently, among 109 infective endocarditis cases, 18% had c-or p-ANCA, and 8% had anti-PR3 or anti-MPO [5]. This report illustrates a diagnostic difficulty between SBE and specific involvement of GPA with no classical systemic symptoms.…”
Section: Discussionmentioning
confidence: 89%
“…In the present report, blood cultures were negative and p-ANCA anti-MPO positive. However, this type of valvular involvement associated with ANCA may be encountered in SBE [5]. c-ANCA are most often encountered in SBE, but p-ANCA are also described.…”
Section: Discussionmentioning
confidence: 99%